White Castle : the evaluation of an upstanding prehistoric enclosure in East Lothian - Connolly, David (Access archaeology., 2021)
This publication describes the results of a four-year research programme of archaeological works (2010-2013), at the later prehistoric enclosure of White Castle, East Lothian. The excavations demonstrated a clear sequence of enclosure development over time, whereby the design and visual impact often appeared to be more important than defence alone.